Exploring the Role of Ellipsis in Creepypasta: A Narrative Analysis - Lutfia, Nabila Shauma (Syntax Literate, 2025)
This paper explores the use of ellipsis in critical discourse analysis, with a specific focus on creepypasta stories. Ellipsis, a linguistic phenomenon where certain elements of a sentence are omitted, plays a crucial role in these horror narratives by creating suspense, suggesting hidden meanings, and streamlining communication. By examining various forms of ellipsis in creepypasta, the study seeks to identify patterns and interpret their implications for narrative structure and emotional impact. The research employs a qualitative approach, analyzing creepypasta texts from a variety of online sources where ellipsis is a key feature. The analysis focuses on the context, function, and potential interpretations of ellipsis in these stories. By comparing the findings with existing theories and frameworks in linguistics and discourse analysis, the study aims to shed light on how ellipsis contributes to the tension and eeriness that define the creepypasta genre. The results suggest that ellipsis serves multiple functions in creepypasta, from heightening suspense to avoiding redundancy.Additionally, the study underscores the importance of understanding ellipsis in these horror narratives to fully appreciate their unsettling atmosphere and to interpret subtle cues that drive the storyline. These insights contribute to a deeper understanding of how linguistic structures can enhance the effectiveness of horror storytelling, with implications for both literary analysis and practical communication in suspenseful contexts.